2011
DOI: 10.1016/j.biomaterials.2011.08.047
|View full text |Cite
|
Sign up to set email alerts
|

The use of injectable sonication-induced silk hydrogel for VEGF165 and BMP-2 delivery for elevation of the maxillary sinus floor

Abstract: Sonication-induced silk hydrogels were previously prepared as an injectable bone replacement biomaterial, with a need to improve osteogenic features. Vascular endothelial growth factor (VEGF165) and bone morphogenic protein-2 (BMP-2) are key regulators of angiogenesis and osteogenesis, respectively, during bone regeneration. Therefore, the present study aimed at evaluating in situ forming silk hydrogels as a vehicle to encapsulate dual factors for rabbit maxillary sinus floor augmentation. Sonication-induced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
221
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 254 publications
(238 citation statements)
references
References 48 publications
14
221
2
1
Order By: Relevance
“…The relative expression level for each gene of interest was normalized to that of the housekeeping gene GAPDH. 38 …”
Section: Reverse Transcription and Real-time Polymerase Chain Reactiomentioning
confidence: 99%
“…The relative expression level for each gene of interest was normalized to that of the housekeeping gene GAPDH. 38 …”
Section: Reverse Transcription and Real-time Polymerase Chain Reactiomentioning
confidence: 99%
“…Similarly, Zhang et al 42 found that the single VEGF from the silk gel or silk scaffold only promoted angiogenesis and more tissue infiltration into the gel or scaffold, in which no bone regeneration was observed, while combining VEGF and BMP-2 released from the silk gel or silk scaffold could promote angiogenesis and new bone formation. 48,49 Besides, graft motion in the bone tunnel could be inevitable in ACL reconstruction model, which impeded bone regeneration. It was verified that interfacial implant movement will lead to soft tissue formation instead of bone.…”
mentioning
confidence: 99%
“…Others are able to be injected. Hyaluronic acid (Martinez-Sanz et al, 2012), gelatin (Yamamoto et al, 2006) and silk (Zhang et al, 2011) based hydrogels have all shown the capacity to deliver BMP-2 and produce bone in animal models. However, many of these hydrogels comprise of animalderived proteins that can bring associated costs and disease risk.…”
mentioning
confidence: 99%